(untitled) (Research, Society and Development, 2022)
The objective of the study is to analyze, in the literature, the impact of remote teaching on the psychic illness of nursing students in the COVID-19 pandemic. The study followed the Integrative Review method, with data analyzed using Bardin’s Thematic Categorical Content Analysis. Nine studies were selected for analysis. Greater adherence to the teaching model took place after the emergency adaptations arising from the COVID-19 outbreak. Stress factors related to remote teaching among nursing students differ according to the sociodemographic profile. The sudden changes generated by social distancing cause different responses among students. Academic issues were the main source of anxiety and distress. Remote teaching has become a favorable experience for self-reliance and stimulating the development of problem-solving capacity. The restrictive measures and the change to the remote model demonstrated a challenge to the various core components of educational institutions. New investments are fundamental in the development of remote learning.